Peningkatan Pertumbuhan Phalaenopsis amabilis (L.) Blume secara In Vivo dengan Thidiazuron (TDZ) - Nur Cahyani, Evi; Nintya Setiari; Yulita Nurchayati (Jurnal Hortikultura Indonesia, 2025)
Phalaenopsis amabilis (L.) Blume is a type of orchid widely used as an ornamental plant and as a parent species in breeding programs. Overexploitation and slow vegetative growth make this species a target for ex-situ conservation efforts, which can be supported through the application of nutrients and plant growth regulators, such as Thidiazuron (TDZ). This study aimed to examine the effect of TDZ application and determine the optimal concentration of TDZ for the growth of P. amabilis. The research was conducted from November 2023 to January 2024 in Tembalang, Semarang, using a Completely Randomized Design (CRD) with a single factor, namely TDZ concentration (0.25, and 50 ppm). The observed parameters included the length and width of existing leaves, the number and emergence time of new leaves, leaf color, the number and emergence time of new roots, and stomatal density. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test. The results showed that TDZ significantly enhanced the length and width of existing leaves, the number and emergence time of new leaves, and stomatal density in P. amabilis. Thidiazuron (TDZ) also affected leaf color. The best concentration for promoting leaf growth was 25 ppm TDZ. Keywords: conservation, cytokinin, growth regulator, vegetative